Gastropod Microhabitat Associations and Niches in Seagrass Ecosystems on Donrotu Island, South Jailolo District, West Halmahera Regency - Sunarti; Yuyun Abubakar; Riyadi Subur; Salim Abubakar; Rina; Adi Noman Susanto; Ariyati H. Fadel (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Gastropods are included in the mollusk phylum which is known to be well-associated with seagrass ecosystems. The gastropod community is an important component in the food chain in seagrass beds and ecologically seagrass beds have an important role in the ecosystem. Seagrass ecosystems are habitats and food sources for fish and other aquatic biota. One of the biota commonly found in seagrass beds is Gastropods. This study was conducted to know the composition of gastropod species, types of gastropod associations, and gastropod microhabitat niches in seagrass ecosystems on Donrotu Island. Gastropod sampling was carried out at low tide. The gastropod samples found were then put into a plastic bag that already contained a label. Furthermore, the gastropod samples were brought ashore to count the number of individuals of each type and determined based on morphological characteristics such as shell shape, shell color, shell mouth opening, and spiral circle based on Dharma (1992) instructions. Based on the results of the study, the composition of the types of gastropods found in the seagrass ecosystem on the island of Donrotu was as many as 13 species. There were 13 pairs of gastropod types that had positive associations and 65 pairs of no associations. The type of gastropod that has the widest habitat niche is Cypraea tigris and the narrowest are Naticarius coillei and Pseudovertagus aluco.